Remdesivir: Mechanism and Effectiveness for Coronavirus Disease 2019 (COVID-19) - Neldi, Vina; Suharjono, Suharjono (Pharmaceutical Sciences and Research, 2020)
Currently, coronavirus disease 2019 (COVID-19) is a very serious health problem. The World Health Organization (WHO) has characterized this disease as a pandemic. Recommendations related to vaccines and drugs are not available yet because they are still in the clinical trial phase, and one of the superior drugs is remdesivir which has an antiviral activity. Several clinical trials of this drug are being carried out with the aim of evaluating its safety and efficacy in COVID-19 patients. There are two clinical trials with completed recruitment status, which are NCT04257656 and NCT04280705. NCT04257656 showed that remdesivir had faster time for clinical improvement in severe COVID-19 patients compared to placebo although it was not found to be statistically significant. Moreover, NCT04280705 showed that remdesivir was superior compared to placebo in shortening the recovery time in hospitalized adults with COVID-19. Gilead Sciences is also conducting clinical trials on this drug, and WHO has also conducted a solidarity trial and INSERM DisCoVery trials on remdesivir. Based on two clinical trials completed, satisfactory results are shown in patients with remdesivir therapy compared with patients who received placebo, although it is very important to wait for the results of other ongoing clinical trials to strengthen the evidence of the safety and efficacy of this drug.